Owner Exposure through Firm Disclosure - Müller, Maximilian A.; Peter, Caspar David; Urzúa I., Francisco (The Accounting Review, 2023)
ABSTRACT We study whether firms avoid financial disclosures to preserve their owners' financial privacy. We find that firms named after their owner, for whom firm disclosure would more directly expose owner information, are more opaque. Eponymous owners prefer firm opacity when disclosure exposes sensitive owner information with social stigma, in rural and anticapitalist areas, and in insider-oriented settings with high secrecy and distrust. When firms are forced to disclose, eponymous owners more frequently change their firms' names, and new firms are less frequently named after their founding owners. These findings indicate that owner-level privacy concerns dampen firm-level disclosure incentives. Data Availability: The data used in this study are available from public sources listed in the paper. JEL Classifications: D82; L51; M41.